2016
DOI: 10.3389/fmicb.2016.01984
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the Attributes of Mucor hiemalis-Derived Silver Nanoparticles for a Synergistic Broad-Spectrum Antimicrobial Platform

Abstract: Driven by the need to engineer robust surface coatings for medical devices to prevent infection and sepsis, incorporation of nanoparticles has surfaced as a promising avenue to enhance non-fouling efficacy. Microbial synthesis of such nanoscale metallic structures is of substantive interest as this can offer an eco-friendly, cost-effective, and sustainable route for further development. Here we present a Mucor hiemalis-derived fungal route for synthesis of silver nanoparticles, which display significant antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(60 citation statements)
references
References 46 publications
3
57
0
Order By: Relevance
“…The antimicrobial effects of silver have been known for decades (20)(21)(22), but despite its historical use and recent inclusion in consumer products (20), little is known about the mechanisms of its antimicrobial action (23)(24)(25)(26). Recent studies have assessed the effects of silver ions and AgNPs in combination with commonly used antibiotics and found that silver potentiates antimicrobial action of antibiotics against planktonically cultured bacterial pathogens (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Small AgNPs (8 to 10 nm) have also shown to be effective at detaching preformed P. aeruginosa biofilms (39) and recent studies from our lab have shown that small AgNPs (10 to 20 nm) synergize the antimicrobial activity of the monobactam antibiotic aztreonam (11).…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial effects of silver have been known for decades (20)(21)(22), but despite its historical use and recent inclusion in consumer products (20), little is known about the mechanisms of its antimicrobial action (23)(24)(25)(26). Recent studies have assessed the effects of silver ions and AgNPs in combination with commonly used antibiotics and found that silver potentiates antimicrobial action of antibiotics against planktonically cultured bacterial pathogens (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Small AgNPs (8 to 10 nm) have also shown to be effective at detaching preformed P. aeruginosa biofilms (39) and recent studies from our lab have shown that small AgNPs (10 to 20 nm) synergize the antimicrobial activity of the monobactam antibiotic aztreonam (11).…”
Section: Discussionmentioning
confidence: 99%
“…AgNPs have shown potent antimicrobial effects in countering E. coli, S. aureus and S. marcescens [130][131][132] . It also showed antinematode 133 , antiviral 134 , anticancer 135,136 and anti-inflammatory effects 137 .…”
Section: Amla: Antimicrobial Nanoparticlesmentioning
confidence: 99%
“…Furthermore, the Ag NPs possess no resistance among the wide-range of microbes (Aziz et al, 2016). Furthermore, the Ag NPs possess no resistance among the wide-range of microbes (Aziz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition of having antibacterial properties, the Ag NPs are also effective against some of the fungal strains (e.g., Candida albicans and Aspergillus niger) . Furthermore, the Ag NPs possess no resistance among the wide-range of microbes (Aziz et al, 2016). In this study, initially we have blended TiO 2 NPs with the solutions of cellulose acetate in acetone/water to form colloidal solution resulting in composite nanofibers using the electrospinning technique.…”
Section: Introductionmentioning
confidence: 99%